Atomic‐Scale Observation of LiFePO4 and LiCoO2 Dissolution Behavior in Aqueous Solutions. (19th September 2018) - Byeon, Pilgyu; Bae, Hyung Bin; Chung, Hee‐Suk; Lee, Sang‐Gil; Kim, Jin‐Gyu; Lee, Hyeon Jeong; Choi, Jang Wook; Chung, Sung‐Yoon
Abstract: Understanding the atomic structure variation at the surface of electrode materials in contact with an electrolyte is an essential step toward achieving better electrochemical performance of rechargeable cells. Different types of water‐based aqueous solutions are suggested as alternative electrolytes to the currently used flammable organic solvents in Li‐ion batteries. However, most research on aqueous rechargeable Li‐ion cells has largely focused on the synthetic processing of materials and resulting electrochemical properties rather than in‐depth atomic‐level observation on the electrode surface where the initial charge transfer and the (de)intercalation reaction take place. By using LiFePO4 and LiCoO2 single crystals, serious P and Co dissolution from LiFePO4 and LiCoO2 into aqueous solutions without any electrochemical cycling is identified. Furthermore, both strong temperature‐dependent behavior of P dissolution in LiFePO4 and very unusual occupancy of Co in the tetrahedral interstices in LiCoO2 are directly demonstrated via atomic‐scale (scanning) transmission electron microscopy. Ab initio density functional theory calculations also reveal that this tetrahedral‐site occupation is stabilized when cation vacancies are simultaneously present in both Li and Co sites. The findings in this work emphasize the significance of direct observation on the atomic structure variation and local stability of the cathode materials. Abstract : Substantial P and Co dissolution from LiFePO4 and LiCoO2 crystals into aqueous electrolytes without any electrochemical cycling is identified. Furthermore, atomic‐scale scanning transmission electron microscopy analysis shows unusual Co occupancy in the tetrahedral interstices in LiCoO2 . The findings emphasize the significance of direct observation on the atomic structure variation and local stability of the cathode materials.